Identification of students' needs for multimedia development in craft and entrepreneurial topic: information technology-assisted learning - Budiarto, Mochamad Kamil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This study aimed to identify the need for multimedia development for craft and entrepreneurship learning. Quantitative descriptive is the research approach used. Data collection techniques using a needs analysis questionnaire and analyzed quantitatively using statistics to find out the means and percentage of responses from the sample. The subjects of this study consisted of 55 students of Class XI IPA of SMA N 1 Susukan, Cirebon. The results of the study report that the need for multimedia development for learning craft and entrepreneurship topic received positive responses from students and was supported by students who have the ability to operate computers, besides that schools had been supported by facilities such as computer laboratories. Given all this time, the module still dominates as a learning medium. This research can be used as a basis for decision making for the stages of developing multimedia learning products.